PENGARUH KEPEMILIKAN MANAJERIAL, LEVERAGE, EMPLOYEE DIFFERENT DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - APIT SUSANTI; KEVIN KEVIN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study was to obtain empirical evidence regarding the effect of the seven independent variables, namely; managerial ownership, leverage, employee different, cash flow, firm size, audit quality, and board size remain on earnings management. The object of research for this study is non financial companies listed on the Indonesia Stock Exchange during the period 2017 to 2019. The research method used for this study is multiple regression, with the sampling technique using the purposive sampling method. The number of samples used for this study amounted to 589 samples studied. This study informs that managerial ownership, employee different, free cash flow, firm size, audit quality, and board size variables have no effect on earnings management, while leverage variables affect earnings management.